Macrophage metalloelastase‐12 is detectable in human seminal plasma and represents a predictor for inflammatory processes in the male genital tract. (16th February 2014) - Urbschat, A.; Paulus, P.; Wiegratz, I.; Beschmann, H.; Hadji, P.; Hofmann, R.; Ochsendorf, F.
Summary Macrophage metalloelastase‐12 (MMP‐12), a protein of the matrix metalloproteinase family, is involved in the breakdown of extracellular matrix in normal physiological processes as well as in disease processes. MMP‐12 is almost exclusively produced by macrophages and is associated with inflammatory disorders. Giving the fact that inflammation negatively influences ejaculate parameters, we investigated a possible presence and correlation of MMP‐12 in seminal plasma with parameters of the ejaculate, especially in leucocytospermic ejaculates. Forty‐two patients who presented for semen analysis were assigned into four groups depending on the result of semen analysis according to the WHO guidelines 2010: normozoospermia (n = 11), OAT (n = 10), azoospermia (n = 10) and leucocytospermia (>1 mio. peroxidase‐positive cells per ml) (n = 11). MMP‐12 was detected by ELISA and was measurable in nearly all seminal plasma samples. Generally, MMP‐12 concentrations were significantly higher in leucocytospermic samples than in nonleucocytospermic ones (P = 0.001). The MMP‐12 levels between the latter nonleucocytospermic groups did not differ. Moreover, MMP‐12 levels correlated with the presence of peroxidase‐positive leucocytes. No correlation with CD 14 positive monocytes/macrophages was detected. In this study, we demonstrate that MMP‐12 is present in seminal plasma and is correlated with inflammatory conditions in human semen and therefore may serve as predictor of ongoing inflammatory processes.